Study of Dengue Outbreak During 2022 Floods Among Patients Presenting to a Tertiary Level Hospital in Nowshera, Pakistan - Saeed, Hafiz Asad; Abbas, Syed Waqar (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the disease burden of dengue due to outbreak during floods among patients presenting to a tertiary level hospital facility.Study Design: Cross-sectional study.Place and Duration of Study: Department of Medicine, Combined Military Hospital, Nowshera Pakistan, from Jul to Nov 2022.Methodology: A sample size of 385 was calculated using the World Health Organization sample size calculator (95% confidence interval, 5% margin of error). Consecutive universal sampling was employed to collect data from confirmed dengue patients in inpatient and outpatient departments. Inclusion criteria encompassed individuals of all ages and genders with clinical and laboratory-confirmed dengue. Patients with negative dengue tests, malaria, typhoid, or Immune Thrombocytopenic Purpura were excluded. Data on monthly dengue cases, comorbidities, recovery, and mortality were analyzed using descriptive statistics through Statistical Package for the Social Sciences software v23.0.Results: Out of the total 925 dengue patients, 583(63.0%) were males, 245(26.4%) were females and 97(10.6%) were children. Dengue occurred most frequently among the age group of 20-35 years (38.1%). Only 6 cases were reported in July 20222 after the first reported case on 25th July 2022. Number of positive cases increased in subsequent months, with 223 cases in August, 425 in September, 210 in October and 61 cases in NovemberConclusion: In the aftermath of the 2022 floods, an increase in dengue cases in Nowshera during August to September 2022 was noted, as compared to the same time frame in 2021.